2014
DOI: 10.5195/ijms.2014.68
|View full text |Cite
|
Sign up to set email alerts
|

Should Research Thesis be a Prerequisite for Doctor of Medicine Degree? A Cross-sectional Study at Jordan University of Science and Technology

Abstract: Background: University based research is an integral part of many prestigious medical schools worldwide. The benefits of student-conducted research have long been highlighted in the literature. This article aims to identify the insights of medical students concerning research training, including perceived hurdles in the way of conducting research, and the utility of a research thesis in acquiring a Doctor of Medicine degree. Methods: A total of 808 medical students at Jordan University of Science and Technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…All these variables are correlated with the fact that the more research proposals and finished research projects a student has, the more chances the student gets for publishing scientific papers. Some universities like Universidad Peruana Cayetano Heredia in Peru, have adjusted their thesis requirements to the ones often used by scientific journals; [ 32 ] also, other studies found that a thesis would be an acceptable pre-requisite for a Doctor of Medicine degree [ 22 , 33 , 34 ]. Although more evidence on this area is needed in order to make appropriate evidence-based decisions in medical curricula and postgraduate curricula, this strategy shows promising as it clearly relates to the opportunity to make scientific publications.…”
Section: Discussionmentioning
confidence: 99%
“…All these variables are correlated with the fact that the more research proposals and finished research projects a student has, the more chances the student gets for publishing scientific papers. Some universities like Universidad Peruana Cayetano Heredia in Peru, have adjusted their thesis requirements to the ones often used by scientific journals; [ 32 ] also, other studies found that a thesis would be an acceptable pre-requisite for a Doctor of Medicine degree [ 22 , 33 , 34 ]. Although more evidence on this area is needed in order to make appropriate evidence-based decisions in medical curricula and postgraduate curricula, this strategy shows promising as it clearly relates to the opportunity to make scientific publications.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial aspect of medical education is research training [1,2]. The GMC (General Medical Council, the United Kingdom's public body which maintains the official register of medical physicians) document 'Outcomes for graduates' states that medical school graduates must be able to 'access and analyse reliable sources of current clinical evidence' and 'interpret and communicate research evidence in a meaningful way for patients to support them in making informed decisions about treatment and management' [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research training is a critical component of medical school education [ 1 , 2 ]. Medical schools are expected to train students in research to meet accreditation standards, to support students’ career prospects and to generate a pool of researchers.…”
Section: Introductionmentioning
confidence: 99%